Non-invasive ventilation in acute respiratory failure in children - Abadesso, C (2012)
BACKGROUND: There is only sparse data on the use of non-invasive ventilation (NIV) in acute respiratory failure (ARF) in infants and children. For this setting we investigated feasibility and efficacy of NIV and aimed to identify early predictors for treatment failure. PATIENTS AND METHODS: Retrospective chart review was performed for all patients treated with NIV for ARF from 2003 to 2010 on an 8-bed pediatric intensive care unit of a tertiary university hospital. RESULTS: Seventy-four patients were treated with NIV. One patient did not tolerate mask ventilation and needed immediate invasive ventilation. Intubation rate of the remaining patients was 23% and mortality 15%. Institution of NIV led to significant improvement of both respiratory and heart rate in all patients within the first hour and to further stabilization within the next 8-10 hr. In patients with NIV success blood gases improved significantly 1-2 hr after starting NIV. Multivariate analysis identified low pH after 1-2 hr to be an individual risk factor for NIV failure. Other factors tested were age, underlying disease, acute respiratory insufficiency versus post-extubation failure (PEF), and 1-2 hr after starting NIV oxygen saturation, respiratory rate, PCO(2) , and FiO(2) . Patients with PEF tended to show better outcomes compared to those with acute respiratory insufficiency. CONCLUSION: NIV can be effective in infants and children with ARF. Low pH 1-2 hr after start of NIV is associated with NIV failure. It may therefore be useful in the decision to continue or stop mask ventilation.